2013
DOI: 10.1186/1475-2875-12-272
|View full text |Cite
|
Sign up to set email alerts
|

Combined DNA extraction and antibody elution from filter papers for the assessment of malaria transmission intensity in epidemiological studies

Abstract: BackgroundInforming and evaluating malaria control efforts relies on knowledge of local transmission dynamics. Serological and molecular tools have demonstrated great sensitivity to quantify transmission intensity in low endemic settings where the sensitivity of traditional methods is limited. Filter paper blood spots are commonly used a source of both DNA and antibodies. To enhance the operational practicability of malaria surveys, a method is presented for combined DNA extraction and antibody elution.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 50 publications
2
69
0
Order By: Relevance
“…To determine 129 molecular prevalence of parasites, DNA was extracted from filter papers using Saponin-Chelex 130 extraction. A nested PCR reaction was performed after the data collection was completed at the 131 Radboud university medical center in The Netherlands, amplifying the P. falciparum and vivax 132 specific 18S ribosomal DNA fragment (37,38). A nested PCR was performed, the nest 1 reaction 133 contained Plasmodium genus specific primers.…”
Section: Malaria Slide and Pcr 125mentioning
confidence: 99%
“…To determine 129 molecular prevalence of parasites, DNA was extracted from filter papers using Saponin-Chelex 130 extraction. A nested PCR reaction was performed after the data collection was completed at the 131 Radboud university medical center in The Netherlands, amplifying the P. falciparum and vivax 132 specific 18S ribosomal DNA fragment (37,38). A nested PCR was performed, the nest 1 reaction 133 contained Plasmodium genus specific primers.…”
Section: Malaria Slide and Pcr 125mentioning
confidence: 99%
“…25 Nested PCR (nPCR) was used to test for the presence of parasite DNA to provide a gold standard measure for current infection. A Chelex-saponin approach was used to extract DNA as described by Baidjoe and others, 24 and the nPCR assay targeting the 18S ribosomal subunit of P. falciparum was used as previously described. 26 Samples that were positive by nPCR were then selected for subsequent analysis to identify allelic diversity using the polymorphic MSP2 region to provide an alternate measure of transmission intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, two blood spot sections per sample were punched, and antibodies were eluted according to work by Baidjoe and others. 24 Antibody prevalence for each antigen was determined after defining a cutoff optical density (OD) based on a standard curve of known antibody concentration using the mixture model and normalized across plates. 20,25 A person was considered to be seropositive if they had normalized OD values above the cutoff for at least one of the antigens tested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Although it is appreciated that DNA degrades over time, there have been few systematic efforts to quantify this degradation, and there is a lack of agreed-upon standards for storage, extraction, and amplification of plasmodial DNA from DBS. Studies have shown that humidity negatively effects DNA quality and that Whatman 3MM and 903 filter paper (Whatman, Clifton, NJ) are ideal for long-term storage.…”
Section: Introductionmentioning
confidence: 99%